Maternal mortality and women's political participation - Sonia R. Bhalotra; Damian Clarke; Joseph Flavian Gomes; Atheendar S. Venkataramani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Raising women's political participation leads to faster maternal mortality decline. We estimate that the introduction of quotas for women in parliament results in a 9-12 per cent decline in maternal mortality. In terms of mechanisms, it also leads to an 8-11 per cent increase in skilled birth attendance and a 6-11 per cent increase in prenatal care utilization. We find reinforcing evidence from the period in which the United States experienced rapid declines in maternal mortality. The historical decline made feasible by the introduction of antibiotics was significantly greater in states that had longer exposure to women's suffrage.
Keywords: I14; I15; O15; 330; gender; maternal mortality; quotas; suffrage; women's political representation